PENINGKATAN KETERAMPILAN BERPIKIR KRTIS DAN RASA INGIN TAHU PADA PEMBELAJARAN IPA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM-BASED LEARNING - Wiwin Fira Nurul Badi'ah; Hasan Subekti; Wahyu Budi Sabtiawan (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
This research aimed to describe the improvement of critical thinking skills and curiosities of Junior High School students’ in science learning using problem-based learning. This research design used one group pretest-postest. This research involved 33 students of class VIII-A of MTs Miftahul Ulum Magerari in Academic Year 2021/2022. This research’s data collection methods included observation , test, and questionnaires. The data analysis technique used in this research was quatitative statistics by using Wilcoxon signed rank test. The results showed that implementation of problem-based learning can improve critical thinking skills and student curiosities in science learning.